Divergent NO2 air pollution trends during the COVID-19 pandemic in Helsinki Metropolitan Area - Gosztonyi, Ákos; Karhula, Aleksi; Juhola, Sirkku; Ala-Mantila, Sanna (IOP Publishing, 2026)
Measures taken during the COVID-19 pandemic reduced key air pollutant concentrations worldwide and highlighted socio-economic disparities in their distribution. While most studies report temporary air quality improvements for lower socio-economic status (SES) groups, we show—using high-resolution spatial socio-economic and air pollution (NO2, nitrogen dioxide) data from the Helsinki Metropolitan Area (HMA), Finland, and applying a generalized difference-in-differences approach—that locations with higher shares of upper-level employees and high-income households experienced the largest reductions in NO2 in 2020, while areas with higher shares of low-income households, lower-level employees, manual workers and social-housing renters saw smaller reductions or non-significant changes in NO2 concentrations. By spring 2021, under less strict containment response policies, NO2 levels rose relative to 2020, though remained below 2019 levels, and the socio-economic pattern partly shifted: higher SES areas showed larger year-on-year increases. However, when compared with pre-pandemic trends, shares of upper-level employees and high-income households were associated with more substantial air quality improvements in 2021 too, whereas most lower SES indicators were associated with weaker improvements or non-significant changes. Taken together, the two spring periods reveal a rather consistent socio-economic stratification in NO2 air pollution trajectories: higher SES locations experienced more significant reductions in NO2 in most instances, whereas most lower SES characteristics were associated with smaller reductions or non-significant changes, indicating more stable air pollution levels. Shares of car owners and private renters are found to exhibit distinct relationships with air pollution changes. As our findings differ from and complement earlier findings from across the globe, we stress the need for more localized research to inform policies aiming to reduce air pollution in an equitable manner in the long run.